Ureteral tumor with morphological features analogous to phyllodes tumor: a unique case with concomitant urothelial carcinoma - Wei Zhou; Linlin Dang; Chuangang Chong; Xiankui Cheng; Yejun Qin; Wenjing Su (BMC, 2022)
Abstract Background Phyllodes tumors belong to a spectrum of biphasic fibroepithelial lesions and are most commonly found in the breast. They are extremely rare in the urinary tract and only one case of bladder phyllodes tumor has been reported. Case presentation We present a 69-year-old man with gross hematuria without an apparent cause. Computed tomography-urography and cystoscopic examination revealed a 5 × 4 cm lesion in the right ureteral orifice. He underwent a laparoscopic nephroureterectomy and partial cystectomy. Postoperative pathology confirmed a leaf-like structure consisting of myxoid stroma and peripheral urothelium. Stromal cells were spindle-shaped and stellate in appearance with no conspicuous cytological atypia or mitosis. The outlining urothelium had varying degrees of dysplasia, while in areas with moderate-to-severe dysplasia, active mitotic activity, abnormal giant cells, and focal early infiltration were observed. Overall, this case had the morphological features of benign phyllodes tumors and concomitant invasive urothelial carcinoma inside. The patient remained disease-free at 7 months after surgery. Conclusion We report the first ureteral tumor with the morphological characteristics of a phyllodes tumor and concomitant invasive urothelial carcinoma inside. Considering the potential for local recurrence of phyllodes tumors and invasive urothelial carcinoma, long-term clinical and radiological follow-up of such lesions are advisable.